1983
DOI: 10.3382/ps.0622394
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Dietary Energy Level and Broiler Body Weight on Abdominal Fat

Abstract: Utilizing a moderate rearing temperature regimen, two trials were conducted to determine the effect of dietary energy level on the amount of abdominal fat deposited when broilers are grown to equal body weight by varying growth time. The most abdominal fat (2.29% average of live weight for male and females) was produced by broilers offered a diet calculated to contain 3325 ME kcal/kg. The least amount of abdominal fat (1.92% average of live weight for male and females) was produced by broilers offered diets ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 7 publications
3
3
0
Order By: Relevance
“…High energy consumption was also shown to increase the relative weights of abdominal fat (Deaton and Lott, 1985; Jones and Wiseman, 1985). A previous study demonstrated that a high energy diet increased the relative weights of abdominal fat compared to a low energy diet (Deaton et al, 1983), which is in agreement with the results of the present study.…”
Section: Resultssupporting
confidence: 94%
“…High energy consumption was also shown to increase the relative weights of abdominal fat (Deaton and Lott, 1985; Jones and Wiseman, 1985). A previous study demonstrated that a high energy diet increased the relative weights of abdominal fat compared to a low energy diet (Deaton et al, 1983), which is in agreement with the results of the present study.…”
Section: Resultssupporting
confidence: 94%
“…These differences could be related to differences in propensity to fatten. In the present study female birds consistently had a much higher percentage of carcass fat and non-carcass fat than did males DEATON et al (1983) found that within each dietary energy level, the abdominal fat in females was higher percentage of live body weight than in males. Also, BECKER et al (1981b) reported that compared with females, males had lower percentage of carcass fat (12 vs. 13.7%).…”
Section: Carcass and Non-carcass Fat Depotssupporting
confidence: 56%
“…Much research demonstrated that high level of dietary energy resulted in higher body weight gain (Pesti & Smith, 1984;Leeson et al, 1996a;Leterrier et al, 1998), and lower FCR (Deaton et al, 1983). In contrast, a dilution of dietary energy and protein increased feed intake (Leeson et al, 1996b), and that was possibly because the broiler is able to control the feed intake based on the energy level in the diet (Leeson et al, 1996b).…”
Section: Discussionmentioning
confidence: 97%